An Exploratory Study on the Reasons and Preferences of Six Malaysian Students on the Video Games Played - Eow, Yee Leng; Baki, Roselan (IJESE, 2008)
The purpose of this study was to explore the reasons why six Malaysian students from upper secondary school are playing video games, types of games and the features preferred. A qualitative method was being used in the study. Purposive sampling was conducted in selecting the students. The findings indicated that students played video games for a great range of reasons. Different students play for different reasons. Some shared common reasons and preferences. A few findings were very specific and never mentioned before in previous researches. However, more research needs to be undertaken in order to address the diversity of students with a bigger sample and different methodology.